Epidemiology and long‐term neurological sequelae of childhood herpes simplex CNS infection. (5th May 2022) - Berkhout, Angela; Kapoor, Vishal; Heney, Claire; Jones, Cheryl A; Clark, Julia E; Britton, Philip N; Vaska, Vikram L; Lai, Melissa M; Nourse, Clare
Abstract : Aim: Herpes simplex CNS infection is a rare but important cause of neurological disability. Long term outcomes after HSV CNS infection in Australia have not yet been fully described. We sought to provide a comprehensive review of HSV CNS infection in children using a retrospective 13‐year evaluation of statewide laboratory and clinical records and a parent survey conducted at least one year after the initial infection. Methods: All positive PCR HSV 1 and 2 results from cerebrospinal fluid (CSF) or brain tissue were obtained from Queensland pathology providers for children aged 0–16 years between 1 January 2005 and 31 December 2017. Clinical data were obtained from patient records and longer‐term outcomes via parent survey at least 1 year after initial infection. Results: Forty‐three children were identified over the 13‐year period, 17 (39.5%) neonates and 26 (60.4%) non‐neonates. The annual incidence for HSV CNS infection in Queensland children aged ≤16 years was 0.3/100 000 (95% confidence intervals (CIs): 0.2–0.4) with neonates at highest risk (incidence 2.5/100 000 live births, 95% CI: 1.5–3.9). HSV 1 was the predominant serotype in both neonates and non‐neonates (9/17, 52.9% neonates and 19/26, 73.1% non‐neonates). Seven (16.3%) children died, five (5/17, 29.4% neonates), directly attributable to HSV CNS infection (all neonates). Twenty‐five (58.1%) had neurological morbidity at discharge (9/17 neonates (52.9%) vs. 16/26 (61.5%) non‐neonates) and 20/27 (74.1%) reported long‐term neurological morbidity at follow‐up (5/9 neonates (55.6%) vs. 15/18 non‐neonates (83.3%)). Seven children (two neonates and four non‐neonates) with long‐term neurological sequelae had no neurological morbidity identified at discharge. Conclusion: Significant long‐term neurologic sequelae were seen in children with HSV CNS infection even in children with no neurological disability identified at discharge from hospital. Careful neurodevelopmental follow‐up of all children is recommended.